(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
The extremely rare condition of molar pregnancy with a coexisting fetus progressing to a viable infant, is reported. At 32 wks, prenatal diagnosis was made by biochemical and sonographic findings in which elevated free ßhuman chorionic gonadotrophic was noted and ultrasound showed a well defined multicystic snow storm like mass connecting with normal placenta. At 37 weeks cesarean section was done due to gestational hypertension, fetal growth restriction and H/O previous one cesarean section. A 2.3 kg male living boy was delivered. The infant did not show any abnormality.The placenta and the connecting hydatidiform mole were delivered. A normal ß HCG level was noted in subsequent follow up. Bangladesh J Obstet Gynaecol, 2015; Vol. 30(2) : 113-115